Indywidualne i społeczne konteksty recepcji mediów. Doświadczenie niemieckie - Michalczyk, Stanisław (Political Preferences, 2017)
Personal and social contexts of media reception. German experiences The fourth question in Lasswell’s model (to whom?) assumes a study and an analysis of media’s publicity and broader reception of the content. This reception should go personally or socially. The personal contexts include amongst others lifecycle and physical and mental limitations. The age plays an important role in media reception. The youth watches less television than the older people, who, on the contrary, are less likely to use electronic forms of communication. Another pattern here is that the older the man is, the longer he reads newspapers and magazines during the day. Important limitations in media reception are due to physical obstacles such as: poor sight and impaired hearing whereas the most significant mental obstacle is depression. The article presents also the problems of reception in a group, that is, when a person watches television or listens to the radio accompanied by other people. The presence of the others modifies all the process, there is a possibility of conversation and commenting the content. A spectacular example of reception in the group is watching football matches. Media can also be received in public space, open for everyone. Nowadays, public spaces are characterized by - as called by the scientists - a communication tyranny. Phone conversations are omnipresent and disturbs everybody. This is a kind of psychological pathology. Media reception depends on the culture, both personal and in a general sense. In Europe, there are differences between North and South that can be explained, among others, by religious factors (Protestantism vs. Catholicism). In the article- as practice shows – we mentioned main German studies, but also in a lesser extent - American and Polish ones. All of them relate to a more general problem of mediatisation and everyday life. Key words: media reception, Personal reception, reception in a group, media vs. culture